2016
DOI: 10.1175/jamc-d-15-0229.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of the Background Diurnal Cycle of Deep Convection around the GoAmazon2014/5 Field Campaign Sites

Abstract: The isolation of the Amazon rain forest makes it challenging to observe precipitation forming there, but it also creates a natural laboratory to study anthropogenic impacts on clouds and precipitation in an otherwise pristine environment. Observations were collected upwind and downwind of Manaus, Brazil, during the “Observations and Modeling of the Green Ocean Amazon 2014–2015” experiment (GoAmazon2014/5). Besides aircraft, most of the observations were point measurements made in a spatially heterogeneous envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
69
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 57 publications
11
69
0
1
Order By: Relevance
“…Giangrande et al (2016) have presented the statistical behaviour of vertical cloud motions as a function of season, instability, and convective inhibition. Burleyson et al (2016) have discussed the diurnal cycle and spatial variability of deep convection among the different GoAmazon sites. Giangrande et al (2017) have also presented an overview of cloud, thermodynamics, and radiation interactions.…”
Section: Knowledge About Cloud Process In the Amazon Acquired During mentioning
confidence: 99%
See 1 more Smart Citation
“…Giangrande et al (2016) have presented the statistical behaviour of vertical cloud motions as a function of season, instability, and convective inhibition. Burleyson et al (2016) have discussed the diurnal cycle and spatial variability of deep convection among the different GoAmazon sites. Giangrande et al (2017) have also presented an overview of cloud, thermodynamics, and radiation interactions.…”
Section: Knowledge About Cloud Process In the Amazon Acquired During mentioning
confidence: 99%
“…Burleyson et al (2016) used 15 years of satellite data to show a heterogeneous spatial distribution of convection that results from numerous local effects of rivers and vegetation cover. Using radar data, Saraiva et al (2016) also found the Amazonas diurnal cycle to vary regionally.…”
Section: Rainfall Sensitivity To Surface Covermentioning
confidence: 99%
“…Recently, the Observations and Modeling of the Green Ocean Amazon (GoAmazon2014/5) Experiment was motivated by demands to gain a better understanding of aerosol, cloud and precipitation interactions on climate and the global circulation (Martin et al, 2016(Martin et al, , 2017. The inability of GCMs to adequately represent cumulus clouds and precipitation over the Amazon highlights one example of the observational needs for future improvement to GCM cloud parameterizations and the larger-scale 10 circulation connections therein (e.g., Richter and Xie, 2008;Nobre et al, 2009;Yin et al, 2013).…”
mentioning
confidence: 99%
“…Giangrande et al (2016) presented the statistical behaviour of cloud vertical motions as function of season, instability and convective inhibition. Burleyson et al (2016) discussed the diurnal cycle and 20 spatial variability of deep convection among the different GoAmazon sites. Giangrande et al (2017) presented an overview of cloud, thermodynamics, and radiation interactions.…”
Section: Knowledge About Cloud Process In the Amazon Acquired During mentioning
confidence: 99%
“…Burleyson et al (2016) used 15 years of satellite data to show a heterogeneous spatial distribution of convection that results from numerous local effects of the rivers and vegetation cover. Saraiva et al (2016), using radar data, also found the Amazonas diurnal cycle to be regionally varying.…”
mentioning
confidence: 99%